Lingupoetic Analysis Of The Poetry Of Nurmuhammad Aziz (In Respect Of Occasional Meaningful Units) - Voxidova, Nozima (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In this article, we conducted a linguopoetic study of the poems of Nurmuhammad Aziz, a young poet with a lively spirit and his own words and style in Uzbek poetry, at the lexical level. Nurmuhammad Aziz is the author of poems that are in tune with the people of today and at the same time harmonized with the memories of the past. It is worth noting that the poet was able to masterfully use the possibilities of our language in his creations and create his own unique style from linguopoetic means, which will be proven in the linguopoetic analysis of the poet's poems below.